An Open-Label, Multicentre Pilot Study of Bosentan in Pulmonary Arterial Hypertension Related to Congenital Heart Disease - Reda Ibrahim; John T Granton; Sanjay Mehta (Canadian Respiratory Journal)
BACKGROUND: Bosentan has been shown to be a safe and efficacious treatment for idiopathic pulmonary arterial hypertension (PAH) and PAH associated with connective tissue disease. However, there are limited studies examining the benefits of bosentan in PAH associated with congenital heart disease (CHD).